Anti-Bacterial Effectiveness Of Cymodocea Rotundata Extract And Assay For Primary Bioactive Composition. - Amiin, Muhammad Kholiqul; Lahay, Almira Fardani (Journal of Aquatropica Asia, 2023)
Anti-bacterial is a compound that can be used to inhibit bacterial growth. The compounds that play a role in damaging the cell membrane are phenols, flavonoids, and alkaloids. The phytochemical compounds above have the potential as natural Anti-bacterial on pathogenic bacteria, for example against Escherichia coli. Escherichia coli is a pathogenic microbe in humans that can cause digestive disorders and disrupt the work system of the stomach organs. Seagrass C. rotundata has compounds that are antibacterial, such as alkaloids, flavonoids, phenols, steroids, and tannins. C. rotundata can be seen in Indonesian waters. However, it has not been widely used. This study aims to determine the difference in concentration of seagrass extract of C. rotundata against E. coli anti-bacterial activity. The research method used was experimental laboratories with different concentrations of seagrass extract (10%, 20%, 30%, and 40%). The results showed that the seagrass extract of C. rotundata was effective as an antibacterial with a middle category, which is the inhibition zone ranging from 5-10 mm. Based on the studies conducted, 72 hours incubation period at 40% concentration was the best concentration to prevent E. coli at the 8.5 mm inhibition zone. Furthermore, bioactive compounds produced by C. rotundata are flavonoid compounds by showing changes in the color of the solution to yellow-orange. In addition, also produces phenol bioactive compounds by showing a change in the color of the solution to greenish, and also produces tannin bioactive compounds by showing a change in the color of the solution to blackish green. The results showed that C. rotundata can be used as a recommendation for the development of Anti-bacterial drugs in the future.